Analisis Pengaruh Early Warning System Dan Risk Based Capital Terhadap Tingkat Solvabiltas Perusahaan - hayati, nur; Denovis, Fanny Oktivia; Arsita, Sari (AKTUARIA, 2023)
To assess the level of financial soundness of a company can be seen from the company's financial statements. Financial reports contain accurate information to find out in more detail about the overall financial condition of a company. All of the company's financial activities will be recorded in a financial report. Every company must have assets, and it is very important to always know their value regularly, both current assets and fixed assets. The financial statements will record any changes in assets that may occur so that the actual value of assets can be known and accounted for. In the financial reports an assessment of the company's financial health can be measured through the Early Warning System, hereinafter referred to as EWS and Risk Based Capital, hereinafter referred to as RBC. This study aims to calculate and analyze EWS and RBC on the level of solvency.Data processing in this study uses smartPLS SEM (Partial Least Square – Structural Equation Modeling) Software. PLS has the ability to explain the relationship between variables and has the ability to carry out analysis in one test. EWS variable (X1) 3,857 is smaller than t-table 1.96. By using a significant limit of 0.05 the EWS significance value (X1) is 0.000. So it can be concluded that partially EWS has a significant effect on the level of solvency. RBC variable (X2) 0.455 is smaller than t-table 1.96. By using a significant limit of 0.05 the significance value of RBC (X2) is 0.649. So it can be concluded that partially RBC has no significant effect on the level of solvency. Simultane ously, the EWS and RBC variables were simultane ously able to explain the solvency level variable of 66.3% and the remaining 33.7% was explained by other variables not hypothesized in the model Keyworrd : Early Warning System, Risk Based Capital ,solvency